Ethnobotanical Insights and Quantitative Evaluation of Medicinal Plant Utilization in Traditional Cosmetic Practices: A Community-Centered Study - Dewi, Ni Luh Kade Arman Anita; Pendet, Ni Made Diah Pusparini; Apriani, Rista; Megawati, Fitri; Udayani, Ni Nyoman Wahyu; Sugijanto, Milyadi; Agustini, Ni Putu Dewi; Javandira, Cokorda (Bali Medical and Wellness Journal, 2025)
Background: Indigenous knowledge about medicinal plants used in cosmetics is an important cultural heritage that needs scientific documentation and preservation. In Terunyan Village, Bali, Indonesia, traditional ethnobotanical practices have been passed down orally through generations. Objective: This study aims to systematically record, identify, and analyze the plant species used by the community for natural cosmetic purposes, and to assess their cultural significance using ethnobotanical indices. Methods: An ethnobotanical survey was carried out using semi-structured interviews with 328 informants selected through purposive sampling. Plant specimens were collected, identified, and voucher samples stored at the Herbarium Hortus Botanicus Baliense (THBB). Quantitative analysis used Use Value (UV) and Fidelity Level (FL) to measure cultural importance and consensus. Results: A total of 24 plant species from 18 plant families were documented for cosmetic use. The most frequently cited species were Aloe vera (UV = 0.180), Cocos nucifera (UV = 0.174), and Solanum lycopersicum (UV = 0.169). Leaves were the most used plant parts (40.85%), and pounding was the main processing method (20.43%). Six species had a fidelity level of 100%, indicating strong cultural agreement. The most common applications were for hair care (35.2%), skin moisturizing (28.7%), and skin brightening (24.1%). Conclusion: This research provides the first detailed documentation of traditional cosmetic plant use in Terunyan Village. It highlights significant ethnobotanical diversity and strong cultural consensus for key species. These findings support the preservation of indigenous knowledge and lay the groundwork for sustainable development of natural cosmetic products.